Research about the association between smartphone use and carpal tunnel syndrome research (Journal of Academic Research, 2025)
Carpal tunnel syndrome (CTS) is the most common upper extremity nerve compression syndrome Which affect the median nerve.Patients with CTS experience reduced sensation, dexterity, and function.Irreversible changes in nerve structure and function due to demyelination and axonal damage can occur in long-standing case.
Keywords: Carpal tunnel syndrome; median nerve; mobile; smartphone; nerve conduction study